The Effect of Total Quality Management on Service Quality Mediated by Digitalization Across Work Units at Regional Representative Office of a Central Bank - Yosep Abriyanto Mamanua; Anton Mulyono Aziz (Eastasouth Institute, 2026)
This study aims to examine the influence of Total Quality Management (TQM) on service quality at regional representative office of a central bank, with digitalization as a mediating factor. The study applied a quantitative explanatory design with a total sampling technique involving all 45 employees across different units at regional representative office of a central bank. Data were collected through structured questionnaires using a likert scale. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. Results show that TQM, digitalization, and service quality are perceived at very high levels. TQM significantly improves service quality both directly and indirectly through digitalization, which functions as a partial mediator. These findings highlight the importance of digital integration in reinforcing management processes and enhancing service performance. This research highlights digitalization as a mediating mechanism that strengthens cross-unit coordination and translates TQM practices into improved service performance in a public financial institution.